New insights on the phylogenetic relationships among the traditional Philodendron subgenera and the other groups of the Homalomena clade (Araceae) - Vasconcelos, Santelmo; Soares, M. Lourdes; Sakuragui, Cássia Mônica; Croat, Thomas Bernard; Oliveira, G.; Benko-Iseppon, A. M. (Molecular Phylogenetics and Evolution, 2018)
Philodendron (Araceae) is one of the largest Neotropical plant genera, with approximately 500 species and at least 1000 species predicted. There is a considerable ecological diversity in the group, although most species occur in the humid forests of tropical America. Despite being relatively well-studied in taxonomic analyses, the relationships among the traditional morphological groups of the genus are not well-established, mainly regarding the three traditional subgenera, referred here as Philodendron sensu lato (s.l.), P. subg. Pteromischum, P. subg. Philodendron and P. subg. Meconostigma, which was recently recognized as a separate genus, Thaumatophyllum. Therefore, the present work evaluates the phylogenetic position and the monophyly of Philodendron s.l. and its three main subdivisions, and the sister groups within the Homalomena clade, which also includes the Neotropical genus Adelonema, the two Asian genera Homalomena and Furtadoa, and the two African genera Cercestis and Culcasia, by means of molecular phylogenetic approaches including chloroplast DNA (atpF-atpH, rpl32-trnL, trnQ-5′-rps16 and trnV-ndhC) and nuclear (ITS2) markers. The monophyly of Philodendron s.l. and its three lineages is confirmed and our analyses corroborate previous morphologic data indicating Thaumatophyllum as sister to the clade formed by P. subg. Pteromischum and P. subg. Philodendron. © 2018 Elsevier Inc.
Keywords: Dna, Chloroplast; Araceae; Bayes Theorem; Classification; Cluster Analysis; Genetics; Geography; Philodendron; Phylogeny; Species Difference; Araceae; Bayes Theorem; Cluster Analysis; Dna, Chloroplast; Geography; Philodendron; Phylogeny; Species Specificity